Study to Address Threats of Acute Respiratory Infections among Congregate Military Populations (ATARI). (4th October 2017) - Coles, Christian; Chen, Wei-Ju; Milzman, Jacqueline Owens; Grigorenko, Elena; Robinson, Scott; Jones, Carol; Moreno, Nicole; Burgess, Timothy; Malone, Leslie
Abstract: Background: More than 90% of active duty personnel receive influenza vaccinations yearly. Despite high coverage, influenza-like illnesses (ILI) remain a frequent cause of missed duty and hospitalizations, particularly in U.S. military recruits. More research is needed on the epidemiology and etiology of ILI to reduce the burden of respiratory infections in congregated military settings. Methods: We conducted a prospective cohort study to assess ILI patterns among US Army recruits in a 9-week basic combat training course at Ft. Benning, GA. Demographic data, vaccination history, and information on recent illness were collected at enrollment in January 2017. Participants were divided into two platoons with staggered biweekly visit schedules. Visits occurred from reception through training, with nasal swabs and symptom surveys (all visits) and blood draws (weeks 8 and 9). Nasal specimens were used to detect clinical and colonizing pathogens using the Diatherix TEM-PCR Respiratory Panel. Results: A total of 90 recruits were enrolled in the study. Twelve recruits were lost due to training attrition in the first week of the study. The participants were male and the mean age was 23 yo (SD 4.9). There were 10 (13%) cases of ILI reported among the 78 remaining participants, 6 in week 1, 3 in week 2 and 1 in week 9. The most frequently detected pathogens in the 10 symptomatic cases were coronavirus (5, 50%), rhinovirus (4, 40%), other enterovirus (3, 30%), and influenza A (2, 20%). Pathogen co-detections were common, 8 out 10 cases were associated with 2 pathogens, representing 7 unique combinations. While rhinovirus and coronavirus were most common among asymptomatic trainees, 10% had detectable influenza A. Detection of multiple pathogens was common in the first two weeks of training (50% among those who had viral detection). The study is still in progress. Conclusion: Symptomatic ILI was associated with coronavirus, rhinovirus, and enterovirus, in addition to influenza in the early weeks of training. Coronavirus and rhinovirus also circulated widely among healthy recruits, along with influenza. The findings will inform ILI control strategies for congregated military trainees. Disclosures: E. Grigorenko, Diatherix Laboratories: Employee, Salary.L. Malone, Diatherix Laboratories: Employee, Salary.